2005
DOI: 10.1001/archneur.62.10.1556
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Vascular Risk Factors at Midlife and the Risk of Dementia and Alzheimer Disease

Abstract: Background: Vascular risk factors play a role in the development of dementia, including Alzheimer disease (AD). However, little is known about the effect of body mass index and clustering of vascular risk factors on the development of dementia.Objective: To investigate the relation between midlife body mass index and clustering of vascular risk factors and subsequent dementia and AD.Design and Setting: Participants of the Cardiovascular Risk Factors, Aging, and Dementia (CAIDE) study were derived from random, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
740
7
19

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,107 publications
(820 citation statements)
references
References 19 publications
28
740
7
19
Order By: Relevance
“…Several epidemiologic studies have reported an association between high levels of adiposity in adulthood and an increased risk for developing both AD and VD in old age [1,2]. Thus, we hypothesized that individuals with dementia would have a higher FM than those in the control group.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several epidemiologic studies have reported an association between high levels of adiposity in adulthood and an increased risk for developing both AD and VD in old age [1,2]. Thus, we hypothesized that individuals with dementia would have a higher FM than those in the control group.…”
Section: Discussionmentioning
confidence: 96%
“…On the one hand, it has been recently evidenced that high body mass index (BMI) values, and hence adiposity, in adulthood are associated with an increased risk for Alzheimer's disease (AD) and vascular dementia (VD) in late life [1,2]; on the other hand, it is well known that malnutrition and particularly unintentional weight loss are common clinical features in patients with dementia, which occur at the preclinical stage of the disease and are maintained at the follow-up, further aggravating the prognosis of these patients [3].…”
Section: Introductionmentioning
confidence: 99%
“…In one study of 1449 individuals, obesity (BMI 430 kg/m 2 ) at midlife was associated with increased risk of dementia and Alzheimer's disease in later life, after adjusting for sociodemographic variables. 18 Midlife obesity, high total cholesterol and high systolic blood pressure were all significant risk factors for dementia, and had additive effects.…”
Section: Obesity and The Older Womanmentioning
confidence: 99%
“…This gap is especially noteworthy since American Indians have high rates of several conditions that increase risk for poor cognitive functioning, such as alcohol abuse and addiction, 6–8 diabetes, 9,10 traumatic brain injury, 11,12 and overweight/obesity and cardiovascular disease. 13,14 Further, American Indians are disproportionately poor (28.4% compared with 12.4% of the U.S. general population), 15 and low socioeconomic status has been linked to several factors that might affect cognitive ability. These include pre- and postnatal complications, malnutrition, exposure to environmental toxins, increased risk of head injury, and risky health behaviors.…”
mentioning
confidence: 99%